Effects of happy and angry human voice recordings on postural stability in dogs: An exploratory biomechanical analysis - Nadja Affenzeller; Masoud Aghapour; Christiane Lutonsky; Christian Peham; Barbara Bockstahler (PLoS ONE, 2026)
Auditory stimuli are known to induce biomechanical balance responses, influencing postural stability in humans. These responses provide valuable insights into the interaction between auditory perception and physical balance. This study investigates the effect of human voices on postural stability in dogs during static stance. Twenty-three healthy pet dogs were assessed standing on a pressure plate under three auditory conditions: happy voice, angry voice, and no sound. Five conventional Center of Pressure (COP) parameters were analyzed, mediolateral displacement, craniocaudal displacement, support surface (SS_%), average speed (AS) and statokinesiogram length. A significant main effect of condition on SS_% ( F (2) = 4.35, p = 0.019, η² p = 0.165) was found; SS_% values in the angry voice condition (mean = 0.12 ± 0.06) were significantly higher than in the no sound condition (mean = 0.08 ± 0.03; p = 0.026). A K-means cluster analysis of relative COP changes (ΔCOP_%, increase/decrease relative to the no sound condition) revealed two distinct reaction patterns within both sound conditions (ANOVA, all ΔCOP_% parameters, p < 0.01, except AS within happy condition). For happy voices, 57% of dogs exhibited increases across all ΔCOP_% parameters, while 43% showed decreases. In contrast, angry voices led to increased ΔCOP_% parameters in 30% of dogs, with 70% remaining unaffected. A significant difference in Support Surface (ΔSS_%) was found between clusters 1 for happy and angry voices (F = 8.75, p = 0.008). The largest absolute and relative ΔSS_% changes occurred in the angry voice condition. These exploratory findings suggest that the emotional arousal triggered by human voices can have both stabilizing and destabilizing effects on canine balance. Angry human voices were associated with the greatest destabilizing effect.